Highly integrated CO2 capture and conversion: direct synthesis of cyclic carbonates from industrial flue gas. Issue 10 (19th February 2016) - Barthel, Alexander; Saih, Youssef; Gimenez, Michel; Pelletier, Jérémie D. A.; Kühn, F. E.; D'Elia, Valerio; Basset, Jean-Marie
Abstract : The ability of early transition metal halides to capture and convert CO2 from diluted gas flows has been exploited in the cycloaddition of CO2 to epoxides using industrial flue gas as an impure source of CO2 . Abstract : Robust and selective catalytic systems based on early transition metal halides (Y, Sc, Zr) and organic nucleophiles were found able to quantitatively capture CO2 from diluted streams via formation of hemicarbonate species and to convert it to cyclic organic carbonates under ambient conditions. This observation was exploited in the direct and selective chemical fixation of flue gas CO2 collected from an industrial exhaust, affording high degrees of CO2 capture and conversion.